MO525: Iron absorption and phosphate-lowering effects of ferric citrate hydrate are not influenced by gastric secretion inhibitors in patients with chronic kidney disease. (3rd May 2022) - Ito, Kyoko; Mitobe, Yuko; Matsumoto, Yu; Yokoyama, Keitaro
Abstract: BACKGROUND AND AIMS: Ferric citrate hydrate (FC, Riona ® ), an oral iron-based phosphate binder in chronic kidney disease (CKD) patients, is also approved as an iron preparation for iron-deficiency anemia (IDA) in Japan. In the USA, ferric citrate (Auryxia ® ) is approved as a phosphate binder for dialysis-dependent CKD and an iron replacement product for the treatment of IDA in patients with CKD not on dialysis. Ingested iron is dissolved at a low pH of the secreted gastric acid in the stomach, which is an important process for its effective absorption [1 ]. Patients taking gastric acid secretion inhibitors (GASI), such as proton pump inhibitors and histamine-2 receptor antagonists, showed decreased iron absorption and increased risk of iron deficiency, which were dose- and treatment-duration-dependent [2 ]. The increase in the intragastric pH by concomitantly use of GASI might be affected on FC's iron absorption effect. METHOD: We have conducted a retrospective study using data from two previous clinical studies to investigate FC in CKD patients with hyperphosphatemia. A 12-week, phase 3, multicenter, randomized, double-blind, placebo-controlled study in non–dialysis-dependent (ND) CKD patients (FC, n = 60, ; placebo, n = 30) (CTI-111 435) [3 ], and a 52-week, phase 3, multicenter, open-label, dose-titration study in CKD patients undergoing hemodialysis (HD) (FC, n = 180) (CTI-111 437) [4 ] were divided into with or without GASI, and levels of iron and phosphate related parameters were analyzed. RESULTS: In ND patients, approximately 25% in FC ( n = 14) and 50% ( n = 14) in placebo used GASI. Mean [standard deviation (SD)] changes from baseline to end of treatment (EOT) in serum ferritin (ng/mL) were 109.83 (104.46) in FC with GASI, 142.68 (94.28) in FC without GASI, −22.49 (74.85) in placebo with GASI, and −3.43 (43.58) in placebo without GASI (Fig. 1a ). Those in transferrin saturation (TSAT, %) were 16.64 (30.13) in FC with GASI, 17.07 (17.56) in FC without GASI, 2.86 (14.68) in placebo with GASI, and 1.31 (9.75) in placebo without GASI (Figure 1b ). The mean (SD) dose of FC with or without GASI were 3240 mg/day (approximately 778 mg ferric iron) with GASI ( n = 14) and 3445 mg/day (approximately 827 mg ferric iron) without GASI ( n = 46), respectively. In HD patients, approximately 50% ( n = 95) used GASI. Mean changes (SD) from baseline to EOT in serum ferritin (ng/mL) were 166.32 (153.70) with GASI and 155.16 (139.47) without GASI, and in TSAT (%) were 16.60 (19.44) with GASI and 16.02 (18.81) without GASI, respectively. The mean (SD) dose of FC with or without GASI were 2619 mg/day (approximately 629 mg of ferric iron) with GASI ( n = 95) and 2854 mg/day (approximately 685 mg or ferric iron) without GASI ( n = 85), respectively. In both studies, there were no differences in the changes from baseline to EOT in serum phosphate between with or without GASI. CONCLUSION: GASI did not interfere with iron absorption and phosphate-lowering effects of FC in CKD patients with hyperphosphatemia.